Functional Constipation in Children: Pathophysiology, Diagnosis, and Management - Gupta, Rajeev (British Journal of Healthcare and Medical Research, 2024)
Functional constipation (FC) is a common paediatric issue, affecting 3% of children worldwide [1]. The condition can have a significant impact on the quality of life for both children and their families. This review focuses on the current understanding of the pathophysiology, diagnosis, and management of FC in children, with an emphasis on recent advances and guidelines. Recognising and addressing constipation in children is crucial for their overall health and well-being. Due to the unique developmental, behavioural, and physiological differences between children and adults, a tailored and comprehensive approach is essential for effective management in paediatric populations.